A short-term longitudinal study of correlates and sequelae of attachment security in autism. Issue 2 (4th March 2018) - Rozga, Agata; Hesse, Erik; Main, Mary; Duschinsky, Robbie; Beckwith, Leila; Sigman, Marian
ABSTRACT: In this short-term longitudinal study, 30 preschool-aged children with autism were first observed in Ainsworth's Strange Situation Procedure and, separately, interacting with the primary caregiver in the home. One year later, each child completed both a developmental assessment and an observational assessment of empathic responding. Behaviors typical for children with autism were distinguished from behaviors suggestive of relationally based attachment disorganization. Forty-five percent of the children were classified as securely attached. The secure group demonstrated language skills superior to those of the insecurely attached group, concurrently and during the follow-up. Compared to parents of children who were insecurely attached, parents of securely attached children were rated as more sensitive. Compared to both organized insecure and disorganized children, secure children were rated as more responsive to an examiner's apparent distress during the follow-up relative to their ratings at intake, whereas empathy ratings of children with insecure classifications did not increase. Importantly, attachment security was associated with empathy above and beyond the contribution of children's language level. These results indicate that the sequelae of attachment security in autism may be similar to those documented for typically developing children.